Comparison of Radical Nephroureterectomy and Partial Ureterectomy for the Treatment of Upper Tract Urothelial Carcinoma - Zhang, Jianzhong (Biomed Res Int, 2018)
This study aimed to compare the oncological and renal outcomes of partial ureterectomy (PU) versus radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). UTUC patients' clinical information was reviewed, and progression-free survival (PFS), overall survival (OS), and kidney function were collected. The mean follow-up period was 59 (6–135) months in the RNU group and 34.5 (5–135) months in the PU group. The mean operation time in the PU group was 141 (64–340) min, which is significantly shorter than the RNU group (P < 0.01). Regarding kidney function at one year or two years after operation, the PU group had significantly improved mean estimated glomerular filtration rate (eGFR) levels and a remarkably decreased constitution of patients with chronic kidney disease (CKD) III or higher group (P < 0.05). There was no significant difference in PFS and OS between the RNU group and the PU group (P > 0.05). Multifactor Cox regression analysis indicated that age and the preoperative CKD stages were independent risk factors for poor kidney functions of UTUC patients. Compared to patients in RNU group, patients in PU have no significant difference in survival time but have shorter operation time, shorter hospital stay, and improved kidney functions.